Variety of genetic defects in GnRH and hypothalamic–pituitary signaling and development in normosmic patients with IHH - Kałużna, Małgorzata; Budny, Bartłomiej; Rabijewski, Michał; Dubiel, Agnieszka; Trofimiuk-Müldner, Małgorzata; Szutkowski, Kosma; Piotrowski, Adam; Wrotkowska, Elżbieta; Hubalewska-Dydejczyk, Alicja; Ruchała, Marek; Ziemnicka, Katarzyna (Frontiers in Endocrinology, 2024)
Introduction: Normosmic isolated hypogonadotropic hypogonadism (nIHH) is a clinically and genetically heterogeneous disorder. Deleterious variants in over 50 genes have been implicated in the etiology of IHH, which also indicates a possible role of digenicity and oligogenicity. Both classes of genes controlling GnRH neuron migration/development and hypothalamic/pituitary signaling and development are strongly implicated in nIHH pathogenesis. The study aimed to investigate the genetic background of nIHH and further expand the genotype-phenotype correlation.Methods: Sixty-seven patients with nIHH were enrolled on the study. NGS technology and a 38-gene panel were applied.Results: Causative defects regarded as at least one pathogenic/likely pathogenic (P/LP) variant were found in 23 patients (34%). For another 30 individuals, variants of unknown significance (VUS) or benign (B) were evidenced (45%). The most frequently mutated gene presenting P/LP alterations was GNRHR (n=5), TACR3 (n=3), and CHD7, FGFR1, NSMF, BMP4, NROB1 (n=2 each). Monogenic variants with solid clinical significance (P/LP) were observed in 15% of subjects, whereas oligogenic defects were detected in 19% of patients. Regarding recurrence, 17 novel pathogenic variants affecting ten genes were identified for 17 patients. The most recurrent pathogenic change was GNRHR:p.Arg139His, detected in four unrelated subjects. Another interesting observation is that P/LP defects were found more often in genes related to hypothalamic-pituitary pathways than those related to GnRH.Conclusions: The growing importance of the neuroendocrine pathway and related genes is drawing increasing attention to nIHH. However, the underestimated potential of VUS variants in IHH etiology, particularly those presenting recurrence, should be further elucidated.